Rekonstruksi Moral Remaja dalam Konseling Keluarga Berbasis Filsafat Idealisme: Integrasi Etika Dialogis dan Pedagogi Reflektif - Dwi Anggraini Rahman; Dhalia Soetopo; Nur Angelica Qurotul A’yun (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
The increasing moral challenges faced by adolescents in contemporary society have raised concerns regarding the effectiveness of family-based moral education and counseling practices. This study examines how the philosophy of idealism can contribute to the reconstruction of adolescent moral values within the context of family counseling. Epistemologically, idealism is grounded in the philosophical traditions of Plato’s Idea of the Good, Kant’s Categorical Imperative, and Hegel’s concept of Sittlichkeit, all of which emphasize that ultimate reality is spiritual and that moral values originate from reason. Employing a philosophical hermeneutic and genealogical approach, this study analyzes the conceptual intersections between Educational Philosophy and Family Counseling. The findings reveal a complementary relationship in which Educational Philosophy emphasizes moral formation through rationality and character cultivation, whereas Family Counseling focuses on resolving value conflicts through empathic and dialogical interactions. The integration of these perspectives generates an idealism-based family counseling framework that combines dialogical ethics and reflective pedagogy. This framework not only addresses adolescent behavioral conflicts but also facilitates the restoration of conscience through moral reconstruction within contemporary, pluralistic family systems. Consequently, idealism-based family counseling offers a holistic and philosophically grounded approach to fostering adolescents’ moral development within the family ecosystem.